BlindSense: An Accessibility-inclusive Universal User Interface for Blind People - Khan, A.; Khusro, S.; Alam, I. (Engineering, Technology & Applied Science Research, 2018)
A large number of blind people use smartphone-based assistive technology to perform their common activities. In order to provide a better user experience the existing user interface paradigm needs to be revisited. A new user interface model has been proposed in this paper. A simplified, semantically consistent, and blind-friendly adaptive user interface is provided. The proposed solution is evaluated through an empirical study on 63 blind people leveraging an improved user experience in performing common activities on a smartphone.